1998
DOI: 10.1046/j.1365-2133.1998.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar pustulosis: a clinical and immunohistological study

Abstract: Pustulosis palmoplantaris (PPP) is a common chronic skin disease, which is very resistant to treatment. It is not known why the lesions are located in the palms and soles. There are few studies of the disease and in particular studies of the histology. Fifty-nine patients with PPP answered a questionnaire concerning their medical history and 39 of them were clinically examined. Biopsy specimens were taken from involved skin in 22 of the 39 patients and studied immunohistologically for tryptase+ mast cells, EG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
183
2
11

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(213 citation statements)
references
References 20 publications
17
183
2
11
Order By: Relevance
“…In PPP, accumulation of activated neutrophils and elevated levels of IL-8 in lesional areas are prominent (19,20,45). We herein confirm increased production of IL-8, as well as the closely related CXC chemokine Gro-␣, to be typical for PPP compared with a number of other cytokines and chemokines (such as MIG and IL-6), which are also elevated in eczema, and TNF-␣, being only moderately elevated in PPP.…”
Section: Discussionsupporting
confidence: 56%
“…In PPP, accumulation of activated neutrophils and elevated levels of IL-8 in lesional areas are prominent (19,20,45). We herein confirm increased production of IL-8, as well as the closely related CXC chemokine Gro-␣, to be typical for PPP compared with a number of other cytokines and chemokines (such as MIG and IL-6), which are also elevated in eczema, and TNF-␣, being only moderately elevated in PPP.…”
Section: Discussionsupporting
confidence: 56%
“…70 Some studies have shown the presence of an abnormal portion of the acrosyringium in the epidermis of patients with PPP, suggesting its participation in the etiopathogenic process of pustule formation. 60 Furthermore, nicotinic receptors expression is altered in the epidermis of patients with PPP, and nicotine would lead to an inflammatory response with altered expression of acetylcholinesterase (acetylcholine degrading enzyme), resulting in lesions of PPP. 70 The triggering mechanism of inflammation is unknown.…”
Section: Palmoplantar Pustulosismentioning
confidence: 99%
“…In general, the disease is persistent and painful, causing the functional impairment of patients. [59][60][61][62] Because PPP shares some common features with pustular psoriasis, some authors consider it a localized form of this disease.…”
Section: Palmoplantar Pustulosismentioning
confidence: 99%
See 2 more Smart Citations